Risk factors and clinical characteristics of occult pancreaticobiliary reflux in benign gallbladder diseases - Yukai Xiang; Chen Qiu; Hai Hu; Jingli Cai; Gang Zhao; Anhua Huang; Anan Xu; Chuanqi He; Cheng Zhang; Yulong Yang; Zhaoyan Jiang (BMC Gastroenterology)
Abstract Background This study aimed to elucidate the clinical characteristics of occult pancreaticobiliary reflux (OPBR) in benign gallbladder diseases, including gallbladder stone (GS), gallbladder polyp (GP), and gallbladder adenomyomatosis (GA). Methods We studied 578 patients with a normal pancreaticobiliary junction undergoing surgery for gallbladder diseases between December 2020 and January 2022. Of these, 80 patients had elevated bile amylase levels (> 110U/L) and were classified as OPBR patients; 498 comprised the control group. Patients fell into four groups: Group A (GA), Group B (GS alone), Group C (GS and GP), and Group D (GP alone). Results OPBR occurred in 16.2% of GS cases, 7.2% of GP cases, and 20.3% of GA cases. Patients with OPBR were typically older and more likely to have GS but less likely to have GP. In GS patients, OPBR incidence correlated with stone size, peaking at 48% in cases of gallbladder sludge (< 3 mm). OPBR incidence was highest in Group A (20.3%), followed by Group B (16.6%), Group C (8.9%), and Group D (4.8%). Patients over 50 and those in Groups A and B faced higher OPBR risk. In Group A, gallbladder sludge and hyper-gamma-glutamyltransferase were risk factors, while in Group B, gallbladder sludge and age over 50 were risk factors. No specific features associated with OPBR were found in Groups C and D. Conclusion In conclusion, GP isn’t associated with OPBR, irrespective of GS presence. However, in GS alone or GA patients, gallbladder sludge should raise OPBR concerns, necessitating tailored clinical attention.